1976
DOI: 10.1002/hlca.19760590719
|View full text |Cite
|
Sign up to set email alerts
|

13C‐NMR. Spectroscopy of Naturally Occurring Substances. XLV. Iboga Alkaloids

Abstract: Summary. The carbon shifts of the Iboga-type alkaloids catharanthine, voacanginc, coronaridine, ibogaine, dihydrocatharanthine and epiibogamine were recorded and correlated with the conformation of the natural bases. A 13C-NMR. analysis of heyneaninc determined its C(19) configuration and a similar study of cpihcyneanine proved its structure.In connection with problems of structure determination and synthesis of indole alkaloids of the Iboga type it became of importance to apply 13C-NMR. spectroscopy thereto. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…In this work, the ethyl acetate basic fraction of the root bark of T. catharinensis yielded twelve indole alkaloids: coronaridine (1), coronaridine hydroxyindolenine (2), voacangine (3), voacangine hydroxyindolenine (4), ibogamine (5), heyneanine (6), voacristine (7), voacristine hydroxyindolenine (8), 3-oxo-coronaridine (9), 3-hydroxycoronaridine hydroxyindolenine (10), vobasine (11) and voachalotine (12). This is the first report on the presence of the alkaloids 7, 8, 9 and 12 in T. catharinensis while 10 has never been described.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this work, the ethyl acetate basic fraction of the root bark of T. catharinensis yielded twelve indole alkaloids: coronaridine (1), coronaridine hydroxyindolenine (2), voacangine (3), voacangine hydroxyindolenine (4), ibogamine (5), heyneanine (6), voacristine (7), voacristine hydroxyindolenine (8), 3-oxo-coronaridine (9), 3-hydroxycoronaridine hydroxyindolenine (10), vobasine (11) and voachalotine (12). This is the first report on the presence of the alkaloids 7, 8, 9 and 12 in T. catharinensis while 10 has never been described.…”
Section: Resultsmentioning
confidence: 97%
“…Of the 12 alkaloids isolated 10 are of the ibogan class and the other 2 of the corynanthean class. They were identified by comparison with published data (UV, IR, 1 H NMR, 13 C NMR and MS) 3,5,[9][10][11][12][13][14] .…”
Section: Resultsmentioning
confidence: 99%
“…By far the largest group of alkaloids studied is that having an indole chromophore, but this group includes alkaloids with very diverse structures. It was at first thought that these various structural types would need to be considered separately but, since calculation showed that the SCS values for the different types were similar, the compounds have been dealt with as one group, consisting of the following types 12,23,29,79,98,112 two indole c h r o r n o p h~r e s ;~~~~~~~~.~~ various dimers, one half of which has an indole moiand miscellaneous alkaloids with an indole chromophore not belonging to the preceding…”
Section: Resultsmentioning
confidence: 99%
“…The known indole alkaloids, ibogamine (2), 12,13 olivacine (3), 14,15 NMR experiments, which were also used to complete and unambiguous 1 H and…”
mentioning
confidence: 99%